في تحسين مهارة القراءة لدى الطلاب بالمدرسة المتوسطة الإسلامية الحكومية 3 أغام canva باستخدام وسيلة suggestopedia تأثير طريقة - Jum'ati Zahra; Nurhasnah (The Future of Education Journal, 2026)
This study aims to determine the effect of implementing the Suggestopedia method using the Canva platform on improving the reading skills of eighth-grade students at State Islamic Junior High School 3agam. The study employs a Quasi-Experimental Design. The research sample consists of two classes: an experimental class taught using the Suggestopedia method with Canva, and a control class taught using traditional methods. The research results were then analyzed using the Cohen's d-test and Cohen's d-test to determine the treatment's impact. Cohen's d-test is an impact measure used to assess the effectiveness of a treatment between two groups. Cohen's score of 1.25 indicates that the Suggestopedia method, using the Canva platform, has a significant impact on improving students' reading skills compared to traditional methods. Therefore, it can be concluded that applying the Suggestopedia method in conjunction with the Canva platform is effective in improving students' reading skills. The researcher chose the Suggestopedia method because it focuses on creating a comfortable, relaxing, and inspiring learning environment, while the Canva platform aims to create an attractive visual presentation.